Open Cholecystectomy: Muscle Splitting Versus Muscle Cutting Incision: A Randomized Study (Community Based Medical Journal, 2015)
The objective of this study is to compare open cholecystectomy through right subcostal incision (Kocher's incision) between muscle splitting and muscle cutting in terms of duration of operation, postoperative pain, length of hospital stay, morbidity and cosmetic outcome. It is a prospective randomized 3 (three) years study which includes 400 patients who underwent open cholecyslectomy from January 2012 to December 2014 at Islamia General Hospital (private) and Al Raji clinic (private) of Mymensingh, Bangladesh. Study shows that open cholecystectomy with muscle splitting has significant advantages over open cholecystectomy with muscle cutting in terms of duration of operation time and postoperative pain. Muscle splitting incision is another option to offer patients who elect to undergo open cholecystectomy with less pain and hospital stay.CBMJ 2015 July: Vol. 04 No. 02 P: 4-7